PENGARUH PROFITABILITAS, FINANCIAL LEVERAGE, NILAI PERUSAHAAN DAN DIVIDEND PAYOUT RATIO TERHADAP INCOME SMOOTHING (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2019) - Fauziah, Nur Annisa Novia; Adi, Suyatmin Waskito (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Earnings information is generally a major concern in assessing the performance or management's accountability and earnings information helps owners or other parties to assess the company's earning power in the future. This causes the management to be compelled to practice income smoothing. The purpose of this study is to analyze the factors that affect income smoothing (income smoothing), namely profitability, financial leverage, firm value and dividend payout ratio. The research population is manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The sampling technique used was purposive sampling technique. The data analysis technique used multiple linear regression. The results showed that profitability, financial leverage, and dividend payout ratio had a positive and significant effect on income smoothing. Meanwhile, firm value has a negative and significant effect on income smoothing.